Lexical Metaphor in Bon Jovi’s Selected Songs - Rosni L Pasaribu; Siti Aisah Ginting (State University of Medan, 2013)
ABSTRACT This thesis deals with Lexical Metaphor as found in the Selected Songs of Bon Jovi. It was conducted to discover the types of Lexical of Metaphor as proposed by Saragih (2006:162) namely Lexical metaphor that is formed by comparing Noun with Noun, Lexical metaphor that is formed by comparing Noun with verb, Lexical metaphor that is formed by comparing Noun with Adjective, Lexical metaphor that is comparing two ideologys or concepts, as symbol of sound. In this researh the writer found out three types of lexical metaphor that applied in the Bon Jovi’s songs. The research was conducted by using descriptive qualitative approach. The subjects of the study is all contetnts of the selected songs of Bon Jovi’s song. The findings indicate that lexical metaphor found in the song include, Nominal-Verbal/Verbal-Nominal (61%),Nominal-Nominal (16%),Nominal-Adjective (13%). Lexical metaphor formed by comparing Noun with Verb was the most dominatly in Bon Jovi’s Selected songs. Because he described the meaning and represented his feelings. Keywords : Lexical Metaphor, Bon Jovi’s Selected Songs